Preventive bacterial translocation and control of Ventilator-Associated Pneumonia: A qualitative study - Yulis Setiya Dewi; Arina Qona'ah; Hidayat Arifin; Rifky Pradipta; Lizy Sonia Benjamin (Faculty of Nursing Universitas Padjadjaran, 2022)
Background: Bacterial translocation is one cause of ventilator-associated pneumonia among patients treated in the Intensive Care Unit. The study aimed to observe critical nurses information about bacterial translocation prevention and ventilator-associated control in clinical settings. Methods: A qualitative phenomenology design was undertaken from July to September 2021. We recruited 40 critical nurses in government and educational hospitals in Surabaya, Indonesia. The in-depth online interview was conducted during the interview process and analysed using Colaizzi’s technique. Results: We emerged five themes that consist of 1) limited of nurse’s competence, 2) unsupported work environment, 3) barrier of human resource management, 4) work motivation, and 5) development of bacterial translocation preventive tools. Conclusion: Prevention of bacterial translocation is needed by developing tools and accessible by nurses. Whereases, the capacity and ability need to be developed by training. Nurses and Hospital Managers consider putting the attention of evidence-based tools in clinical settings.